The vagina problem: a step too far in parentchild sex communication with young children - Conlon, Catherine (My University, 2025)
Parents describe a want for better sex education for their young children compared to their own myth and silence-led experiences while growing up. However, introducing the vagina has proved a challenging step too far for many parents. This study arose from a secondary qualitative data analysis of 20 focus groups with parents in Ireland about how they engage in body and sexuality communication and socialisation practices with young children, aged 4 to 9 years old. Though parents often utilised euphemisms, the language applied to male bodies tended to be generic, while euphemisms for female bodies tended to be family specific. The language used in talking about the female body evaded reference to the vagina and talking about its functions. Protecting the child from knowledge about the sexual body was aligned with maintaining innocence and delaying the progression of the child’s transition into adulthood. Parents demonstrate a commitment to stop using myths but still placed boundaries around their young children’s sex education, albeit boundaries that are being redefined. Perpetuating intergenerational taboos, placing boundaries on the knowledge of the sexual body impacts a child’s ability to fully integrate their body into their sense of self.
PUBLISHED
https://doi.org/10.1080/14681811.2024.2342880
Keywords: parent-child communication, genital naming, young children, secondary qualitative data analysis, Ireland.; Identities in Transformation; Inclusive Society; Making Ireland; Social Services Planning/Policy; Other; Education